Anatomia, nutrição e fisiologia de Echinodorus grandiflorus (Cham. & Schltdl.) Micheli ssp. grandiflorus submetida ao Chumbo - Ribeiro, Estefânia Santos (2014)
The objective of this work was to evaluate the anatomic and physiological mechanisms related to the Echinodorus grandiflorus tolerance when exposed to different concentrations of lead (Pb), since identifying these mechanisms may direct studies in phytoremediation. We conducted experiments with E. grandiflorus plants, exposing them to different concentrations of lead [0, 0.75, 1.5, 3.0, and 9.0 μM of Pb(NO3)2] for a period of 90 days. After the experimental period, we evaluated: leaf gas exchanges, growth characteristics, lead concentrations, macronutrient and micronutrient levels in plant biomass and the modifications in root and leaf anatomy. The data were submitted to analysis of variance and the means were compared by the Scott-Knott test, or submitted to regression analysis. The E. grandiflorus species did not show any modifications in biomass allocation, fresh mass production and in the root system growth under lead contamination. Lead also did not modify stomatal conductance, photosynthetic rate, Ci/Ca ratio, but increased plant transpiration. The plant accumulates up to 113.74 mg kg-1 of lead and this element is mainly compartmentalized in the roots with reduced translocation to the shoots. Modifications occurred in the concentrations of macronutrients and micronutrients, however, without any nutritional restrictions and with evident increase in calcium absorption. The specie’s anatomy does not demonstrate necrosis or evidence of lead intoxication. Modifications also occurred in leaf and root xylem optimizing water and nutrient conduction as well as thickening of endodermis and radicular cortex, which limits the flow of lead to the shoot. Therefore, E. grandiflorus is tolerant to the effects of lead due to growth maintenance, absence of necrosis and improvement in the functionalities of its radicular and foliar tissues, photosynthesis maintenance and mineral nutrition, even accumulating lead in the tissues.